Pengembangan Smart Electric Motorcycle Simulator sebagai Media Pembelajaran Interaktif pada Mata Kuliah Teknologi Kendaraan Listrik & Hybrid di Prodi Pendidikan Teknik Otomotif UNIMED - Derisman, Aken; Nofrial, Nofi; Kurniawan, Ade; Doni, Rahma; Muslim, Muslim; Ridha Fauzi, Muhammad (SURYA TEKNIKA, 2026)
The limited practical facilities in the Electric and Hybrid Vehicle Technology Course in the Automotive Engineering Education Study Program at Medan State University cause the learning process to be dominated by theory. This study aims to develop a Smart Electric Motorcycle Simulator as an interactive learning medium to support students' understanding of electric motorcycle systems. The research method used is Research and Development (R&D) which includes needs analysis, simulator design, simulator table construction, component assembly, functional testing, and expert validation. The results of the study indicate that the simulator is able to operate as designed, characterized by the integrated functioning of the battery, controller, BLDC motor, throttle, protection system, and monitoring device. The simulator is also equipped with wiring terminals that allow students to assemble circuits, operate the system, and monitor voltage and current in real-time via an LCD monitor. In addition to increasing learning interactivity, the modular design of the simulator makes it easy to develop, economical, and suitable for implementation in laboratories with limited facilities. The results of the media expert validation obtained an achievement level of 90% with a very valid category, while the validation of the material expert was 88.89%, which is included in the valid category. Thus, the Smart Electric Motorcycle Simulator is declared suitable for use as a practical learning medium to support learning of electric vehicle technology in vocational education.